Acute lymphoblastic leukemia with bone marrow necrosis as the first clinical manifestation: a pediatric case report - Pan, Liangwu; Lin, Jianren; Zhou, Xiaobo; Huang, Chuanming; Zeng, Yanghui; Fu, Ying (Frontiers in Oncology, 2026)
This paper reports a rare case of a 4-year-old male child with acute lymphoblastic leukemia (ALL) presenting initially with bone marrow necrosis (BMN) as the chief clinical manifestation. The child sought medical attention due to fever, bone pain, and fatigue. Laboratory tests indicated pancytopenia. Initial bone marrow cytomorphology examination revealed disrupted cellular architecture, suggesting possible BMN, and single-site flow cytometry detected no definitive abnormalities, highlighting the diagnostic complexity caused by BMN. Through multi-site bone marrow aspiration and biopsy, the diagnosis was ultimately confirmed as common B-cell ALL (common-B-ALL). Treatment followed the South China Children’s Cancer Collaborative Group SCCCG-ALL-2023 protocol, incorporating blinatumomab immunotherapy based on risk stratification. The child responded well to treatment and is currently in the maintenance chemotherapy phase, with minimal residual disease (MRD) monitoring consistently indicating complete remission. This case emphasizes the importance of early recognition of rare presentations like BMN-onset in pediatric ALL, the necessity of multi-site bone marrow examination, and the crucial role of individualized treatment strategies.